Actividades didácticas para el uso del Hardware Educativo JAAC 2.0 en el subnivel superior de Educación General Básica de la Unidad Educativa Fiscomisional La Dolorosa en el año lectivo 2023-2024 - Guachizaca Sarango, Cristian Israel (2024)
Currently, there are various types of educational resources aimed at fostering learning. Among these is the so-called educational hardware, which includes all physical devices used in an educational context to promote the teaching and learning process. This research addresses the didactic use of the Educational Hardware JAAC 2.0 in the upper sublevel of General Basic Education at the Fiscomisional La Dolorosa Educational Unit for the 2023-2024 academic year. The study is relevant because education is undergoing significant changes with the introduction of technological advancements. For this reason, teachers have a great responsibility to adapt and make use of innovative educational technologies in the classroom. By analyzing the didactic activities that utilize the Educational Hardware JAAC 2.0, the research seeks to fill a gap in the integration and management of educational hardware in the classroom and provide a solid foundation for future interventions. The adopted methodology is exploratory and descriptive in nature, with a quantitative approach and a non-experimental design. The identified population consisted of the institution's teachers, and the sample comprised the teachers from the upper sublevel of General Basic Education. Data collection was carried out using surveys and a questionnaire as the instrument. The findings highlight that educational hardware is adaptable to each subject and allows the creation of didactic activities for different curriculum topics, fostering students' motivation and active participation, and providing valuable insights for teachers. In conclusion, the use of educational hardware with different didactic activities enhances the understanding of the topics covered and guides practical actions in the educational field. Keywords: Didactic activities, educational technologies, educational hardware, playful.